Environmental arguments : product marketing of paper machine - Isola, Tarja (2014)
The aim of this study was to find the products that use less environmental resources than previous products of Metso Paper Inc., Jyväskylä, and how the found characters could have been used in the company’s environmental marketing, i.e. product marketing. Metso Paper Inc., Jyväskylä manufactures paper machines products, and this study was made in 2007. The products were compared with older products of the company; the products that are older solutions or models of the products at the time of the study. The information was gathered by open interviews. At the time of the study the concept of environmental marketing did not exist in Metso Paper, Jyväskylä. The result of this study was that there are no such products that are more environmentally friendly compared to previous products. Therefore there were no characters that could be used in argumentation of product marketing of paper machine products.